2020
DOI: 10.1051/bioconf/20201900021
|View full text |Cite
|
Sign up to set email alerts
|

Role of culture in the emotional response towards komodo dragon in Komodo and Rinca Islands of Komodo National Park

Abstract: Human emotions towards wildlife were seldom considered in wildlife conservation. This study seeks to identify, explore and understand the local communities perceptions and interactions with Komodo dragons. Data were collected from February to April 2018 in Komodo Village and Rinca Village of Komodo National Park, using close and semi-open questionnaires, three-scale Likert statements and interviews with 60 respondents. Although 98.5% considered Komodo as a dangerous species, in total, 60.6% of Komodo villagers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…There was a study conducted in Komodo National Park that examined the impact of human activities on the Komodo dragon, which suggested developing methods to achieve socio-ecological sustainability that benefit people as well as dragon wildlife conservation since there was a potential negative consequence from competition and predation (Praharawati et al, 2023;Ardiantiono et al, 2018). In the same vein, the study by Sunkar et al (2020) confirmed the significance of incorporating local cultural values into conservation support structures. Cole (2006) defines empowerment as the ability of individuals or groups within a community to make decisions about their own lives and exert influence over issues that impact them.…”
Section: Conservation Destinationmentioning
confidence: 94%
See 1 more Smart Citation
“…There was a study conducted in Komodo National Park that examined the impact of human activities on the Komodo dragon, which suggested developing methods to achieve socio-ecological sustainability that benefit people as well as dragon wildlife conservation since there was a potential negative consequence from competition and predation (Praharawati et al, 2023;Ardiantiono et al, 2018). In the same vein, the study by Sunkar et al (2020) confirmed the significance of incorporating local cultural values into conservation support structures. Cole (2006) defines empowerment as the ability of individuals or groups within a community to make decisions about their own lives and exert influence over issues that impact them.…”
Section: Conservation Destinationmentioning
confidence: 94%
“…However, according to research conducted in 1993, the size of the human population in the protected areas was expressed concern in the management plan (Hitchcock, 1993). In contrast, local people in Rinca agreed that Komodo is a protected species (Sunkar et al, 2020). Given these views, this study aims to evaluate the destination development in Komodo National Park from local perspectives to contribute to the research on Tourism Development and Tourism in Protected Areas.…”
Section: Introductionmentioning
confidence: 99%
“…The expulsion of the Komodo dragon is still being carried out. Villagers used to use wooden sticks and pelt stones to repel Komodo dragons that entered the village (Sunkar et al 2020).…”
Section: Barriers Of Komodo National Parkmentioning
confidence: 99%
“…Komodo dragons were first studied and scientifically explained by Owuens in 1912. Komodo dragons are scattered in several parts of Indonesia, especially in the small eastern islands, namely Rinca, Nusa Kode, and Gili Motang (Forth 2013;Sunkar et al 2020). Komodo is an endemic animal that is protected as it is the only ancient lizard that is still alive.…”
Section: Introductionmentioning
confidence: 99%